GEOLOGICAL DRILL CORE DATA PROCESS COMPLETENESS SYSTEM IMPROVEMENT, PT. XYZ - SETYADI (NIM: 29107126), HARMAN
The geological data was one of the main data that was used in an effort to exploration and exploitation mineral deposits. Drill core data which are not completed and are not meet with the standard compliance will make a questionable in the future for the publication of the ore reserve and resource calculation. Weekly report drill core data completeness which reported automatically from the database system during August 2006 - November 2007 presented were not compliance with the standard time cycle approved, which is 90 calendar days. This finding should be improved to reduce the risk of not completed database. The final project is trying to use an approach of the integration Six Sigma cycle of Define-Measure-Analyze-Improve-Control (DMAIC) with the Project Management cycle have selected in this study and to solve the problem faced. This problems has impacted from define and measure risk process which have not well defined, this caused the execution process can not well performed. Control and monitor only performed at the end of the data completeness process, so the occurring problems during the process are late to detect. The insufficient control and monitor along the process, will not raised a warning if in any activities have experience with the bottle neck. Problems were not identifying quickly and easily. Based on the statistical calculation of the drill core data completeness during August 2006 - March 2008, found a total 304 data of 557 data have out of specification, with the Defect per Million (DPMO) is 959,036 or equal to -0.1>. The delaying process along the critical path will resulted the delaying overall data collection process. The calculation result using critical path returning 61.5 + 19.6 days for the drill core data completeness time cycle, which mean the upper control limit, is 81 days, 9 days less than the maximum time standard. The implementation has initiated by doing the re-mapping, identified all cause and select which have the high risk and contribution in the process delay. Those activities have marked as millstone for create a focused control and monitor. Control using completeness status report has designed to make more optimum the existing Enterprise System by doing automatic and integration system. The implementation of the management improvement in the drill core data completeness has improved the performance from Sigma Capacity -0.1A become Sigma Capacity 2.6A.